Assessment of the Magnetic Resonance Imaging Features of Baker’s Cysts and Their Correlation with the Age of Patients - S. A. Chernyad’ev; V. B. Aretinskiy; N. I. Sivkova; A. V. Zhilyakov; N. Yu. Korobova; V. S. Blinov; E. A. Grebenev (Вестник рентгенологии и радиологии)
Objective. To determine the magnetic resonance imaging (MRI) morphological features of Baker’s cysts and to assess their correlation with the age of patients.Material and methods. The investigation was based on the assessment of MRI readings in 37 patients with Baker’s cysts; of them there were 29 (78.4%) women and 8 (21.6%) men. The mean age of the examinees was 60.3 years (25 to 82 years).Results. The mean dimensions of the cysts were measured. Their length, width, and height were 34 ± 2.1 mm, 5 ± 1.2 mm (range 4–31 mm), and 58 ± 2.9 mm, respectively. Their mean thickness was 0.7 mm. Intracystic chondral bodies were detected in 3 (7.5%) cases. These parameters were shown to be unrelated to age. It was found that all cysts were multi-chamber and an average of 6.8 chambers was detected. There was a weak, inversely proportional, statistically significant relationship between the age of the patients and the number of chambers in the cyst. The younger participants of the investigation exhibited no meniscal damage in an overwhelming case (57.1%); whereas complete and incomplete meniscal tears much more often occurred in older patients with Baker’s cysts (from 29 (78.4%) to 34 (91.9%) people, respectively).Conclusion. Degenerative bone and cartilage tissue changes in the joint increase with age, regardless of the cyst sizes.